2010
DOI: 10.1080/15374411003691677
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Processes Associated with Adolescent Distress, Substance Use and Risky Sexual Behavior in Families Affected by Maternal HIV

Abstract: The present study investigated how maternal HIV and mediating family processes are associated with adolescent distress, substance use, and risky sexual behavior. Mother–adolescent (ages 12–21) dyads (N=264) were recruited from neighborhoods where the HIV-affected families resided (161 had mothers with HIV). Mediating family processes were youth aggressive conflict style, maternal bonding, maternal role reversal expectations, and overall family functioning. Results of structural equation modeling indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…Past studies were strictly correlational and did not consider these variables simultaneously. Moreover, many studies examining risky sexual behaviours also used mediators rather than moderators to maximize their understanding of adolescent sexuality (Brakefield, Wilson, & Donenberg, 2012;Kashubeck-West & Szymanski, 2008;Lester et al, 2010;Mezzich et al, 1997). Lastly, the gender invariance of the model will be tested because some sex differences have been reported in the pattern of substance use, psychopathic personality traits and sexual risk-taking (Ruiz, Stevens, Fuhriman, Bogart, & Korchmaros, 2009).…”
Section: The Present Studymentioning
confidence: 97%
“…Past studies were strictly correlational and did not consider these variables simultaneously. Moreover, many studies examining risky sexual behaviours also used mediators rather than moderators to maximize their understanding of adolescent sexuality (Brakefield, Wilson, & Donenberg, 2012;Kashubeck-West & Szymanski, 2008;Lester et al, 2010;Mezzich et al, 1997). Lastly, the gender invariance of the model will be tested because some sex differences have been reported in the pattern of substance use, psychopathic personality traits and sexual risk-taking (Ruiz, Stevens, Fuhriman, Bogart, & Korchmaros, 2009).…”
Section: The Present Studymentioning
confidence: 97%
“…Although this finding has not been consistent across studies (Elkington, Bauermeister, Brackis-Cott, Dolezal, & Mellins, 2009), parenting challenges have been associated with increased externalizing behaviors in children, including substance use (Knowlton, Buchanan, Wissow, Pilowsky, & Latkin, 2008). Maternal bonds have been found to mediate the relationship between level of maternal illness and binge drinking, among other negative behaviors (Lester et al, 2010; Murphy et al, 2009), and parental health lapses have been found to further exacerbate substance use, peer issues, and emotional distress (Lester et al, 2010). …”
Section: Maternal Hiv Status and Daughters’ Alcohol Usementioning
confidence: 99%
“…Such stressors and their destabilizing effects on families and societies may jeopardize healthy development in children. In the context of family loss and chronic illness, children are often pressured to take on additional household and care-giving responsibilities, as well as emotional burdens [2], raising the risk for mental health problems and poor social outcomes, such as school dropout [3, 4]. …”
Section: Introductionmentioning
confidence: 99%